(untitled) (Medico Legal Update, 2020)
Assessment on effects of electronic media on traditional play among higher secondary students in selected schools in Kelambakkam, Kancheepuram District, Tamil Nadu, India. The objectives were to assess the usage of Electronic Media (mobile phones, computers, video games & television) among Higher secondary students, to Assess the effects of Electronic Medias on Traditional Play and to Associate the effects of Electronic Media on Traditional Play with the selected demographic variables. Convenience sampling was used to select 80 Higher Secondary School children. The data collection tools were validated and reliability was established. The data were collected by self-administered questionnaire. The collected data was Tabulated and Analyzed. Descriptive and Inferential statistical method were used. The study shows that 56% of the Children had Moderate positive Impact, 41% of the Children had Optimum Positive Impact and 3% of the students had Minimum positive Impact of Electronic media on Traditional play. There was no significant association between the Effects of Electronic media on Traditional play and the selected demographic variables.